Narrative Review of the Complex Interaction between Pain and Trauma in Children: A Focus on Biological Memory, Preclinical Data, and Epigenetic Processes - Veronica Rivi; Giovanna Rigillo; Ylenia Toscano; Cristina Benatti; Johanna Maria Catharina Blom (Children, 2023)
The incidence and collective impact of early adverse experiences, trauma, and pain continue to increase. This underscores the urgent need for translational efforts between clinical and preclinical research to better understand the underlying mechanisms and develop effective therapeutic approaches. As our understanding of these issues improves from studies in children and adolescents, we can create more precise preclinical models and ultimately translate our findings back to clinical practice. A multidisciplinary approach is essential for addressing the complex and wide-ranging effects of these experiences on individuals and society. This narrative review aims to (1) define pain and trauma experiences in childhood and adolescents, (2) discuss the relationship between pain and trauma, (3) consider the role of biological memory, (4) decipher the relationship between pain and trauma using preclinical data, and (5) examine the role of the environment by introducing the importance of epigenetic processes. The ultimate scope is to better understand the wide-ranging effects of trauma, abuse, and chronic pain on children and adolescents, how they occur, and how to prevent or mitigate their effects and develop effective treatment strategies that address both the underlying causes and the associated physiological and psychological effects.